Association between neutrophil-percentage-to-albumin ratio and mortality among US adults with non-alcoholic fatty liver disease - Zhu, Xinya; Zhao, Weiping; Zhu, Aiyuan; Zhao, Jianyun; Shen, Zheng; Shou, Lujia; Mai, Yiyi; Rong, Fen (Frontiers in Nutrition, 2025)
BackgroundsThere are no studies discussing the relationship between NPAR and mortality among individuals with non-alcoholic Fatty Liver Disease (NAFLD) has not been studied. We aimed to evaluate the correlation between NPAR and all-cause and cardiovascular (CVD) mortality in NAFLD patients in the U.S.MethodsBased on the National Health and Nutrition Examination Survey (NHANES) database from 2003 to 2018, a total of 4,906 participants aged 20 years and older with NAFLD were enrolled in this study. The survival data came from the National Death Index (NDI), which was followed up to 2019. Multivariable cox proportional hazard models were used to explore the relationship between NPAR and all-cause mortality and cardiovascular (CVD) mortality. Restricted cubic spline analysis and threshold effect analysis were applied to assess the nonlinear association between NPAR and all-cause and CVD mortality.ResultsAfter adjusting for multiple covariates, compared to participants with the lowest NPAR reference group (<12.63), those in the highest NPAR group (15.96–26.83) have the hazard ratio for all-cause mortality was 1.979 (95%CI, 1.436–2.729) with P value < 0.001 and for CVD mortality was 2.678 (95%CI, 1.428–5.024) with P value < 0.001. A J-shaped relationship between NPAR and all-cause mortality risk was observed among patients with NAFLD (P for nonlinear = 0.003), whereas there was no nonlinear association with CVD mortality (P for nonlinear = 0.121).ConclusionThe study identified a significant association between elevated levels of NPAR and an increased risk of all-cause and CVD mortality in the United States NAFLD patients.